1997
DOI: 10.1039/a605727f
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the intramolecular transformation of glutathione thiyl radicals to α-aminoalkyl radicals. Thermochemical and biological implications

Abstract: Product studies have been undertaken on the OH ؒ radical-induced oxidation of glutathione in N 2 Osaturated aqueous solutions. Ammonia has been found to be a prominent product with G values around 2.5-2.9 × 10 Ϫ7 J mol Ϫ1 from pH 6 to 10.5. The ammonia is considered to be a product of the disproportionation reaction of the -amino carbon-centred radicals, formed via the intramolecular transformation of glutathione thiyl radicals. At pH ca. 4-6, the ammonia yield decreases due to the fact that the transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 17 publications
7
52
0
Order By: Relevance
“…We reinterpret the published pulse radiolysis data of glutathione and show that the formation of C-centered radicals takes place extremely rapidly, but also that more than one C-centered radical species participates in reaction 3 . While the fast formation of α C-radicals from S-radicals is reported in the literature ( 23 ), we propose the additional formation of β C (or γ C-)-radicals. These reactions have been investigated under both alkaline and acidic conditions and will, therefore, also take place at neutral pH.…”
Section: Introductionsupporting
confidence: 47%
See 1 more Smart Citation
“…We reinterpret the published pulse radiolysis data of glutathione and show that the formation of C-centered radicals takes place extremely rapidly, but also that more than one C-centered radical species participates in reaction 3 . While the fast formation of α C-radicals from S-radicals is reported in the literature ( 23 ), we propose the additional formation of β C (or γ C-)-radicals. These reactions have been investigated under both alkaline and acidic conditions and will, therefore, also take place at neutral pH.…”
Section: Introductionsupporting
confidence: 47%
“…The formation and reactivity of both GS • and GSSG •− radical types have been studied for nearly a half a century (20−23). In the 1980s, it was reported that not only S-centered radicals but also C-centered radicals are part of the chemistry of the GS • radical (24).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a correction of -7.8 kcal/mol was applied to the HAA ΔG ‡ in PHM to give a corrected barrier height of ΔG ‡ = +14.4 kcal/mol, which is consistent with the ∼14 kcal/mol obtained experimentally from the temperature dependence of the intrinsic isotope effect. Similarly, the calculated thermodynamics of HAA from FmG were calibrated to experimental bond dissociation enthalpies (21,22), giving a corrected value of ΔG HAA = +6.7 kcal/mol in PHM (see SI Appendix for details).…”
mentioning
confidence: 99%
“…24,39 The low BDE of α C-H (Gln) is consistent with the experimental observation of the formation of an α C-centered radical at the Gln moiety. 18 On the other hand, the calculated free energy of activation for the H-atom transfer reaction between GS • and the α C-H bond at Gly is hindered by a barrier of 134 kJ mol −1 . 24 …”
Section: Discussionmentioning
confidence: 99%